INTEGRATING HEALTH TECHNOLOGY ASSESSMENT PRINCIPLES IN FORMULARY MANAGEMENT. (22nd March 2016) - Teng, Monica; Khoo, Ai Leng; Zhao, Ying Jiao; Lin, Liang; Lim, Boon Peng
Abstract : Objectives: Effective formulary management in healthcare institutions safeguards rational drug use and optimizes health outcomes. We implemented a formulary management program integrating the principles of health technology assessment (HTA) to improve the safe, appropriate, and cost-effective use of medicine in Singapore. Methods: A 3-year formulary management program was initiated in 2011 in five public healthcare institutions. This program was managed by a project team comprising HTA researchers. The project team worked with institutional pharmacy and therapeutics (P&T) committees to: (i) develop tools for formulary drug review and decision making; (ii) enhance the HTA knowledge and skills of formulary pharmacists and members of P&T committees; (iii) devise a prioritization framework to overcome resource constraints and time pressure; and (iv) conceptualize and implement a framework to review existing formulary. Results: Tools that facilitate drug request submission, drug review, and decision making were developed for formulary drug inclusion. A systematic framework to review existing formulary was also developed and tested in selected institutions. A competency development plan was rolled out over 2 years to enhance formulary pharmacists' proficiency in systematic literature search and review, meta-analysis, and pharmacoeconomic evaluation. The plan comprised training workshops and on-the-job knowledge transfer between the project team and institutional formulary pharmacists through collaborating on selected drug reviews. A resource guide that consolidated the tools and templates was published to encourage the adoption of best practices in formulary management. Conclusions: Based on the concepts of HTA, we implemented an evidence-based approach to optimize formulary management.